Scalar quantum fields in cosmologies with 2+1 spacetime dimensions - Sánchez-Kuntz, Natalia; Parra-López, Álvaro; Tolosa-Simeón, Mireia; Haas, Tobias; Flörchinger, Stefan (Physical review, 2022)
Motivated by the possibility to use Bose-Einstein condensates as quantum simulators for spacetime curvature, we study a massless relativistic scalar quantum field in spatially curved Friedmann-Lemaître-Robertson-Walker universes with d=2+1 spacetime dimensions. In particular, we investigate particle production caused by a time-dependent background geometry, by means of the spectrum of fluctuations and several two-point field correlation functions. We derive new analytical results for several expansion scenarios.